Emergence in mind - Macdonald, Graham; Macdonald, Cynthia, 1951- (Oxford : Oxford University Press, 2010)
There have long been controversies about how minds can fit into a physical universe. In 'Emergence in Mind' a distinguished group of philosophers discuss whether mental properties can be said to 'emerge' from physical processes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy of mind; Emergence (Philosophy)